(untitled) (Scientific journal of the Fergana State University, 2023)
Thу article is devoted to the history of the CEFR program and how it has been affected to varying degrees as a result of reforms in Uzbekistan in recent years. It discusses the problems that have arisen since the introduction of the CEFR program and their solutions. As a result of the direct introduction of CEFR into the education system, some problems are emerging. This indicates that the CEFR is a relative language program and that each country, each educational institution, must implement it in its own context.